The Role of Parasocial Relationship and Fear of Missing Out in Generation Z’s Purchase Intention - Rista Nabilla; Asri Rejeki (Al-Qalam Institue, 2026)
The rapid evolution of influencer marketing has fundamentally transformed the consumption behavior of Generation Z in Indonesia, where digital figures have become the primary authority in purchasing decisions. This study aims to analyze the influence of Parasocial Relationship (PSR) and Fear of Missing Out (FoMO) on purchase intention, as well as to measure the simultaneous contribution of both variables to Generation Z. Utilizing a quantitative correlational approach, data were gathered through online questionnaires from 130 respondents selected via purposive sampling. Data analysis was performed using multiple linear regression techniques to examine the relationships among variables. The results indicate that PSR and FoMO exert a positive and significant influence on purchase intention, both partially and simultaneously. These findings confirm that an intimate emotional bond with an influencer (PSR) and social anxiety driven by missing out on trends (FoMO) act as the main drivers of transactional urgency among young consumers. The implication of this study provides a new perspective for marketing practitioners to balance authentic personal narrative strategies with ethical urgency. This research highlights the importance of maintaining relationship credibility between influencers and audiences for a healthy, meaningful, and sustainable digital economic ecosystem amid fast-moving trend dynamics in Indonesia.